Bleached pulp and fermentable sugars from sugarcane pith bagasse - Vargas-Radillo, J. Jesús; Salazar-Ríos, Edgar; Barrientos-Ramírez, Lucia; Pérez-Centeno, Armando; Rentería-Urquiza, Maite; Rodríguez-Rivas, Antonio; Navarro-Arzate, Fernando; Rutiaga-Quiñones, José (Instituto de Ecología, A.C., 2016)
Pith bagasse is a sub-exploited residue produced in large quantities in sugar mills and paper mills. It is a mixture of parenchyma cells, vessels and small-size cellulose fibers. The content of carbohydrates and lignin in pith is similar to the fiber fraction. In order to take advantage of this significant carbohydrate content, two distinct processes were applied to the pith material: Pulping-bleaching, and enzymatic hydrolysis. In the first case the pith was treated with pre-hydrolysis, soda pulping, bleaching and beating process, obtaining bleached pith-pulp with 68% ISO brightness and 0,38% of residual lignin. The largest increase in strength (77,6% increase in tensile index, IT) happened when 30% of this unbeaten pulp was added to paperboard, while with 10% of refined bleached pulp, IT increased in 43,8%. In the second, the pith was enzymatically hydrolyzed. In 6 h of hydrolysis a yield of 86,6% of fermentable sugars was obtained in both, cooked pith-pulp and bleached pith-pulp, close to 100% hydrolysis of carbohydrates present in the substrate, which is significant because the yield of fermentable sugars from untreated pith was only 26,1%.